Analisis Pengaruh Hubungan Inflasi Dan Nilai Tukar Rupiah Di Indonesia - Nur Rahmah Maysarah; Lucky Widyarto; Christoforus Erik Pb; Indra Suhendra; Cep Jandi Anwar (Peneliti.net, 2023)
Inflation is a macro indicator that is often used to determine economic conditions. Achieving low inflation will have a positive impact on the economy. The value of the Rupiah exchange rate is very important to pay attention to, because if the Rupiah exchange rate against foreign currencies decreases it will have a very negative effect on the Indonesian economy and also the capital market. The increasingly open movement of globalization is reflected in the rise and fall of international trade barriers. An increase in international trade volume can cause local currency exchange rate fluctuations. The purpose of this study is to find out whether T-1 inflation (the previous year) has an effect on the rupiah exchange rate for the 2012-2022 period. This study uses a quantitative research approach. The data used in this research is secondary time series data from the official websites of BPS and Bank Indonesia